A new statistical thermodynamic mechanism for quantum mechanics - Alpert, Martin (Frontiers in Physics, 2022)
A new quantum mechanics mechanism theory based on statistical mechanics is introduced. This theory is based on corresponding changes in the number of states with associated energy changes at the observer and observed occurring at observer’s 1) reset and, 2) the observation. It is shown that: a) the change in the number of states has different consequences than determining the “value” obtained at observation, where each state is a possible interaction between the system and environment. Bits, as a measure of information content, are numbered in the discrete cell size of a state. For validating the introduced mechanism, two experiments are proposed. The first experiment is to determine the spatial and temporal characteristics of energy changes as well as how they are correlated to the observer and observed during the entire measurement process. The second experiment is to determine timing between changes in the number of states. It is anticipated that that these experiments will show how no time delay can infer the existence of an entangled process and hence, explain delayed choice observations. Moreover, they will also show that bits not stored are lost, so when the number of inputs is greater than the number of outputs, an energy change occurs, and interference is observed (wave characteristics). Conversely, if the number of inputs equals the number of outputs, no energy change occurs, and no interference is observed (particle characteristics). It is envisioned that, upon validating this mechanism theory, it will further the understanding of the measurement process and entanglement’s involvement in that process.